Assessment by the Scheimpflug imaging system of corneal clarity and anterior segment properties in rosacea patients - Erman Bozali; Duygu Yalınbaş Yeter; Mustafa Tosun; Anıl Selim Apa (Sociedade Brasileira de Dermatologia, 2024)
Abstract Objective To evaluate the effects of rosacea on ocular surface changes such as alterations in dry eye parameters, corneal densitometry, and aberrations, in comparison with healthy controls. Methods A total of 88 eyes of 44 patients diagnosed with rosacea and 88 eyes of 44 healthy controls were enrolled in this cross-sectional study. All participants underwent a comprehensive dermatologic and ophthalmic examination and Tear Break-Up Time (TBUT) and Schirmer-1 tests were performed. The rosacea subtype and Demodex count and OSDI scores of all participants were recorded. Corneal topographic, densitometric, and aberrometric measurements were obtained using the Scheimpflug imaging system. Results The mean age of the 44 patients was 41.2 ± 11.0 years of whom 31 (70.5%) were female. The mean TBUT and Schirmer-1 test values were significantly decreased and OSDI scores were significantly increased in the rosacea group compared to healthy controls (p < 0.01 for all). The most common subtype of rosacea was erythematotelangiectatic rosacea (70.4%). The severity grading of rosacea revealed that 18 (40.9%) patients had moderate erythema. The median (min-max) Demodex count was 14.0 (0-120) and the disease duration was 24.0 (5-360) months. The comparison of the corneal densitometry values revealed that the densitometry measurements in all concentric zones, especially in central and posterior zones were higher in rosacea patients. Corneal aberrometric values in the posterior surface were also lower in the rosacea group compared to healthy controls. The topographic anterior chamber values were significantly lower in the rosacea group. Study limitations Relatively small sample size, variable time interval to hospital admission, and lack of follow-up data are among the limitations of the study. Future studies with larger sample sizes may also enlighten the mechanisms of controversial anterior segment findings by evaluating rosacea patients who have uveitis and those who do not. Conclusion Given the fact that ocular signs may precede cutaneous disease, rosacea is frequently underrecognized by ophthalmologists. Therefore, a comprehensive examination of the ocular surface and assessment of the anterior segment is essential. The main priority of the ophthalmologist is to treat meibomian gland dysfunction and Demodex infection to prevent undesired ocular outcomes.